Optimisation of the ingredients for the development of low-calorie basundi - Singh, Mayank; Kaushik Khamrui; Writdhama G Prasad (Indian Journal of Dairy Science, 2021)
In the present investigation the levels of sucralose (55-75 ppm), a mixture of maltodextrin and D-sorbitol (1:1) (4-6%) and inulin (0.5-1.5%), were optimised using General Factorial Design. The combination resulting in maximum desirability of 0.851 with formulation viz., sucralose (65 ppm), a mixture of maltodextrin and D-sorbitol (5%), and inulin (1.5%) was selected as an optimised solution based on the sensorial, rheological and colour attributes of the product. The scores of quality attributes varied significantly when the level of anyone factor changed to interact with the remaining two factors. An increase in flavour score was observed with an increase in inulin level and a mix of bulking agents while a decrease in varying sucralose from 55 to 65 ppm. The decrease was due to an undesirable medicinal flavour perceived in the product. The interaction among the factors gave the unique value for which no common trend was observed. The sensory scores viz., flavour, colour and appearance, consistency and overall acceptability were 7.70, 7.69, 7.54, 7.64, respectively, and the colour attributes viz., L*, a*, b* value, whiteness and brownness index were 78.21, 1.67, 17.79, 71.79, and 29.85, respectively. The calorie content in optimized basundi was reduced to 130.71 C/100g on comparing with control basundi (189.55 C/100g). The optimised basundi contained 65.30±0.01% moisture, 1.11±0.01% fat, 8.49±0.32% protein, 9.22±0.61% lactose, 10.90±0.12% carbohydrates (maltodextrin), 142.12 ppm sucralose, and 1.49±0.18% ash. The fat content was reduced to 1.11% with the complete eradication of sucrose. Thus, the total calorie value was reduced to 58.84 C/100g. All samples had pseudoplastic flow behaviour with consistency coefficient 14.3±1.30 and 32.6±2.10 mPa.s, respectively.